Central nervous system mucormycosis in a patient with hematological malignancy: A case report and review of the literature. Issue 12 (December 2022) - Shirane, Shuichi; Najima, Yuho; Fukushima, Kazuaki; Sekiya, Noritaka; Funata, Nobuaki; Kishida, Yuya; Nagata, Akihito; Yamada, Yuta; Konishi, Tatsuya; Kaito, Satoshi; Kurosawa, Shuhei; Yoshifuji, Kota; et al.
Abstract: Invasive mucormycosis is a refractory fungal infection. Central nervous system (CNS) mucormycosis is a rare complication caused by infiltration from the paranasal sinuses or hematogenous dissemination. Here, we present a case of a brain abscess, due to mucormycosis, diagnosed using burr craniotomy. A 25-year-old Japanese woman with relapsed-refractory acute lymphoblastic leukemia underwent cord blood transplantation (CBT). The patient experienced prolonged and profound neutropenia, and oral voriconazole was administered as primary antifungal prophylaxis. The patient received a conditioning regimen on day −11 and complained of aphasia and right hemiparesis on day −6. Magnetic resonance imaging (MRI) revealed a T2-weighted high-intensity area in the left frontal cortex. A brain abscess was suspected, and liposomal amphotericin B (L-AMB) administration was started. The patient underwent CBT as scheduled and underwent neutrophil engraftment on day 14. Although the patient achieved complete remission on day 28, her consciousness level gradually deteriorated. MRI revealed an enlarged brain lesion with a midline shift sign, suggesting brain herniation. Craniotomy was performed to relieve intracranial pressure and drain the abscess on day 38, and a diagnosis of cerebral mucormycosis was confirmed. The L-AMB dose was increased to 10 mg/kg on day 43. Although the patient's consciousness level improved, she died of hemorrhagic cystitis and aspiration pneumonia. Cerebral mucormycosis should be suspected if neurological symptoms are observed in stem cell transplant recipients. Prompt commencement of antifungal therapy and debridement are crucial because mucormycosis has a poor prognosis.